Congenital hypothyroidism with seizures: a case report - Ann Vivian Sproul; Yogavijayan Kandasamy (Hygeia Press di Corridori Marinella, 2016)
Congenital hypothyroidism (CH) is defined as thyroid hormone deficiency, present at birth. It is seen in 1:4,000 births and is caused by an anatomical defect, known as thyroid dysgenesis (underdevelopment or unusual location of the thyroid gland), by abnormal biosynthesis of the thyroid hormones (dyshormogenesis), inborn errors of metabolism, genetic mutations or iodine deficiency. If untreated, severe neurological impairment develops. However, newborn screening programs have improved outcomes greatly, through early diagnosis and treatment. Clinical manifestations are often subtle at birth, due to the placental transfer of thyroxine (T4), thus making diagnosis in the first few days of life difficult. Increased levels of thyroid stimulating hormone (TSH) and low levels of T4 are confirmatory for this disorder. We describe the case of a baby with CH who presented with neonatal seizures: a rare clinical presentation. Our case highlights the need to eliminate CH, as a cause of seizures, so that treatment can be initiated even more promptly to optimize neurological sequelae and outcome.